UJI TEKNIS TRAKTOR KUBOTA TIPE M9540 PADA PENGOLAHAN LAHAN KERING DI KELURAHAN WAILAN, KOTA TOMOHON - Gabriela A. Assa; Ruland Rantung; Robert Molenaar; Daniel P.M. Ludong (COCOS, 2014)
ABSTRACTSoil tillage aims to create physical soil condition suitable for plant growth. It does that by improving soil water and air association as well as water movement in soil. Mechanical soil tillage requires lots of energy; therefore, good tillage practice needs to carefully consider a proper soil condition in order to get the required result. A technical test to Kubota tractor type M9540 with 95 horsepower was done in this research, as it has never been done before in specific soil condition, topography, and climate of the North Sulawesi. The objectives of this research were to measure aspects of effective field capacity and field efficiency, fuel consumption, to calculate tillage cost and tractor Break Even Point. Soil tillage results were also evaluated by measuring soil bulk density, water infiltration and moisture content before and after tillage. The test was done by cultivating the dry land through performing primary and secondary tillage, each was carried out in three replications. The results show that average effective field capacity for first primary tillage was 1.55 m2/second (0.56 ha/hour), second primary tillage was 1.75 m2/second (0.63 ha/hour), and the secondary tillage was 2.72 m2/second (0.98 ha/hour) with average field efficiency was 77.40%, 80.72%, and 56.17% respectively.Total time to complete the first and second primary tillage was 0.11 hour and 0.10 hour, with diesel fuel consumption of 64.17 liters/ha, and 55.44 liters/ha. The secondary tillage required 0.06 hour and fuel consumption of 28.72 liters/ha.The primary and secondary tillage were found to influence the soil moisture content, bulk density, and rate of water infiltration. Tillage basic cost is calculated as Rp.1.765.683 /ha to result a hire charge of Rp. 1.942.251 /ha, and the tractor break-even point was found to be 552 ha/year.Keywords: Tractor, tillage